Surgeons' knowledge regarding the diagnosis and management of pancreatic cancer in China: a cross-sectional study - Bing-Qi Li; Li Wang; Jian Li; Li Zhou; Tai-Ping Zhang; Jun-Chao Guo; Yu-Pei Zhao (BMC, 2017)
Abstract Background Pancreatic cancer is rare but highly malignant. Studies have shown that surgeons' knowledge closely links to the correct diagnosis and treatment outcomes of pancreatic cancer. The purpose of this study was to survey current surgeons' knowledge regarding pancreatic cancer. Methods A cross-sectional study was conducted among 705 surgeons who attended the 2011 China Surgical Week's meeting in Beijing. A questionnaire regarding the risk factors, clinical manifestations, diagnosis, and treatment of pancreatic cancer was used. Surgeons' answers were analyzed and compared among different regions, levels of hospital, and professional ranks. Results Most surgeons had a correct knowledge toward the risk factors, diagnosis, and management of pancreatic cancer. However, several knowledge gaps were identified. They include "The association between type 2 diabetes and pancreatic cancer", "The most common histologic type of pancreatic neoplasm", "the typical clinical symptoms of pancreatic cancer", "The accuracy of ultrasound in screening pancreatic cancer", "Enhanced CT in the diagnosis of pancreatic cancer", and "Which is more superior between MRI and CT in the diagnosis of pancreatic cancer". We also found that overall surgeons' responses did not depend on their geographic locations, but on hospital levels and professional ranks. Surgeons working at level three hospitals had better knowledge than others in certain areas and resident surgeons had fewer correct answers in some areas. Conclusions Although most surgeons have a good knowledge in most areas related to the diagnosis and treatment of pancreatic cancer in China, certain knowledge gaps exist, particularly among trainees and those from low level hospitals. Continuing medical education programs to improve these knowledge gaps should be implemented.